SPMETS: Sequential Pattern Mining in Exceptional Text Streams using WEKA Tool - Saranya, U; Padmavathi, S (International Journal of Computer Sciences and Engineering, 2025)
Checking and making sense of the rich and continuously refreshed document in an online medium can yield important data that allows users and association increase useful Information about progressing events and consequently make quick move. This calls for powerful ways to precisely screen break down and summarize the Important data present in an on the web. Customarily term-based and word-based approaches used for data sifting. Theme demonstrate has used for discovering unseen topics in a set of qualification. Term-based and Word-based approaches have disadvantage which are polysemous and synonymy. The animal of propensity mining procedure used in field of theme demonstrating generates show for discovering more significant and discriminative topics from accumulation of documents.